Structure of the NS2B-NS3 protease from Zika virus after self-cleavage - Phoo, Wint Wint (2017)
The recent outbreak of Zika virus (ZIKV) infections in the Americas represents a serious threat to the global public health. The viral protease that processes viral polyproteins during infection appears as an attractive drug target. Here we report a crystal structure at 1.84 Å resolution of ZIKV non-structural protein NS2B-NS3 protease with the last four amino acids of the NS2B cofactor bound at the NS3 active site. This structure represents a post-proteolysis state of the enzyme during viral polyprotein processing and provides insights into peptide substrate recognition by the protease. Nuclear magnetic resonance (NMR) studies and protease activity assays unravel the protein dynamics upon binding the protease inhibitor BPTI in solution and confirm this finding. The structural and functional insights of the ZIKV protease presented here should advance our current understanding of flavivirus replication and accelerate structure-based antiviral drug discovery against ZIKV.